Hepatitis B vaccination coverage and associated factors among children living in northwest Ethiopia city administrations: A community-based study - Mekuanint Geta; Asrat Hailu; Yimtubezinash Woldeamanuel (Public Health in Practice)
Objective: A study was being conducted to assess the current vaccination coverage, dropout rates, and associated risk factors in children under 15 years old in northwest Ethiopia. Study design: A community-based cross-sectional survey. Methods: A community-based survey was conducted in northwest Ethiopia from January to March 2024. A two-stage cluster-sampling technique was used to select a representative sample. Sociodemographic information, vaccination history, and epidemiological risk factors were collected using a pre-tested, structured questionnaire. Data analysis was performed using SPSS version 23, employing descriptive statistics, chi-square test, and logistic regression model. Associations of vaccination determinants were investigated, with a p-value <0.05 considered statistically significant. Results: In the study, 808 children were surveyed, with 53.0 % being female and 53.0 % were born at hospitals. Most (52.5 %) were under 5 years old, with a mean age of 5.4 ± 3.5 years. Seven hundred thirty four (90.8 %) had received at least one dose of the hepatitis B vaccine, and 82.7 % had received three doses, with a 9.0 % dropout rate. Among children completely vaccinated against hepatitis B, 366 (54.8 %) were in the age group of 1–4 years. The vaccination coverage was 85.4 %, 82.9 %, and 76.5 % in Bahir Dar, Gondar, and Debre Markos, respectively. Several factors have been identified as predictors of complete hepatitis B vaccination in children, including mothers who attended primary school (AOR = 2.9; 95 % CI: 1.4–5.8) and those with secondary education or higher (AOR = 2.2; 95 % CI: 1.3–4.0), married mothers (AOR = 2.5; 95 % CI: 1.5–4.3), and mothers aged 21–30 years (AOR = 2.7; 95 % CI: 1.3–5.6) and those aged 31–40 years (AOR = 2.8; 95 % CI: 1.4–5.5) were more likely to have their children fully vaccinated. Additionally, children born in hospitals (AOR = 2.4; 95 % CI: 1.3–4.3) or health centers (AOR = 4.0; 95 % CI: 2.2–7.4), increased access to vaccination services (AOR = 2.5; 95 % CI: 1.5–4.3), children aged 1–4 years (AOR = 3.1; 95 % CI: 1.7–5.5) and 5–9 years (AOR = 3.8; 95 % CI: 2.1–7.1) had higher HB vaccination coverage. Conclusion: The complete hepatitis B vaccination coverage in this study was lower than the WHO recommendation for developing countries. Therefore, enhancing the promotion of facility delivery and ensuring easy access to vaccines are crucial for improving children's vaccination coverage.